(untitled) (Research, Society and Development, 2020)
Animal-assisted activities (AAA) consist of activities that aim for recreation, entertainment and distraction through contact with animals. This bond can bring several benefits to those assisted in emotional and physiological terms. The goal of this work is to evaluate the response of mentally ill patients to AAA. Two AAA sessions were held at an institution for the mentally ill in the city of Pelotas, in a recreation room. Before and after contact with the dogs, the heart rate and blood pressure of those being assisted were measured. The faces scale was also applied at both times. The sessions lasted an average of one hour and 11 patients participated. Some patients preferred to perform activities with direct contact with the dog, whereas others preferred recreational dog-themed activities. The dogs acted as motivators and prompted the assisted patients to engage in the activities for longer periods of time, thus, promoting relaxation. Blood pressure and heart rate post activities in most patients remained stable or decreased. The activities helped the patients to become more communicative, show affection for the dogs and the team involved. The faces scales indicated that everyone maintained the initial perception or improved it. In conclusion, AAA provided welfare benefits to patients with mental illnesses in terms of maintaining blood pressure and heart rate, improving socialization, behavioral aspects, and self-perception of happiness.